Conceptual IoT Implementation in Post-Pandemic School Activities: A Case Study in Elementary Schools - Yulisetiani, Septi; Hatta, Puspanda (IJIE (Indonesian Journal of Informatics Education), 2021)
Many studies empirically discuss the use of technology in overcoming pandemics in education. Generally, research discusses the use of technology in online teaching and learning activities. When viewed from the information technology layer, these studies focus on discussing the use of the software layer. This study examines conceptually about the utilization of the hardware layer in information technology, especially Internet of Things infrastructure which is used to help the community in carrying out their daily activities in the new normal era. Conceptual ideas are applied by taking a case study in education, especially in the elementary school environment. The urgency is that there are many stakeholders in the elementary school environment, especially children who need extra attention and supervision in carrying out post-pandemic activities outside the house. These stakeholders are a group at risk of being exposed to the virus because the majority have not received protection in the form of vaccination and the level of adherence to health protocols is low. This creates a risk for vulnerable groups, namely children, families, and teachers. It is necessary to integrate cyber physical systems that help minimize these risks. This conceptual idea describes the concept of IoT technology to minimize the risk of virus transmission and the strategies that allow it to be applied in the elementary school environment. With a top-down approach, it describes how the IoT system protects children and teachers from going to school, doing activities in the school environment, participating in learning in class, to completing learning.